Description of a new species and redescriptions of two rare species of Parapercis (Perciformes: Pinguipedidae) from the tropical Pacific Ocean - Ho, Hsuan-Ching (Zootaxa, 2015)
Parapercis johnsoni sp. nov. is described based on 19 specimens from Marquesas Islands, French Polynesia. It differs from congeners in having a combination of the following characters: dorsal-fin rays V, 21; anal-fin rays I, 17; pectoral-fin rays modally 17; pored lateral-line scales modally 52 or 53; predorsal scales 7 or 8; transverse scale rows 3.5 or 4 + 14 or 15; total gill rakers on 1st gill arch 13–16; single row of teeth on vomer; 6 large canines at front of lower jaw; and a distinct coloration. Two rare species, P. flavescens Fourmanoir & Rivaton, 1979 and P. fuscolineata Fourmanoir, 1985, are redescribed based on the types and newly identified specimens. Comments on other species occurring in the area are provided.